STERILIZATION OF GRAINS USING IONIZING RADIATION: THE CASE IN GHANA - Enu, Richard; Enu, Patrick (European Scientific Journal, ESJ, 2014)
Grains are important dietary components, providing many nutrients including vitamins, minerals, protein, and complex carbohydrates. The objective of the study therefore was to determine the minimum dose of Gray that would be required to kill insects on or inside the grains without affecting the viability for experimental work and there by render the grains free of infestation for laboratory experiments. In this investigation, maize and cowpea seeds were infested with Sitophilus zeamais and Callosobruchus maculatus respectively for 52 days each. The cultures were further divided into fifty grams (50g) each and put into 42 plastic containers. The seeds were then irradiated in a Co-60 gamma cell with doses 40Gy [Gray], 80Gy, 150Gy, 200Gy, 300Gy and 500Gy. The irradiated seeds were then examined for the number of insects alive in each case and the effect of the gamma irradiation on viability of the grain seeds. It was concluded that both Sitophilus zeamais and Callosobruchus maculatus were susceptible to gamma doses between 200Gy-500Gy. As much as 100% mortality was recorded for both insect at some doses. Germination tests subsequently carried out showed that gamma irradiation had no effect on seed viability.